On a collection of freshwater and estuarine crabs (Crustacea: Brachyura) from Mindanao Island, the Philippines - Lagare, Nickel Jean S.; Mapi-Ot, Emmarie F.; Molina, Ziljih S.; Neri, Jemateo B.; Nuñeza, Olga M.; Mendoza, Jose Christopher E. (Zootaxa, 2020)
The brachyuran fauna of the large southern Philippine island of Mindanao is poorly known, with only a few freshwater and estuarine crab species described or recorded in the last 30 years. Renewed interest in crab biodiversity has led to recent, small-scale surveys (2016–2019) of freshwater and estuarine habitats in various localities in Mindanao, which have yielded a good diversity of brachyuran crabs. As a result, a total of 26 species of brachyuran crab, representing 6 families (Hymenosomatidae, Oziidae, Gecarcinidae, Sesarmidae, Varunidae, and Ocypodidae), are reported here. Of these, 15 species are new records for the main island of Mindanao, 6 of which are also new records for the Philippines. Remarks on the taxonomy, distribution, and natural history of these species are also provided.